The Influence of CEO Ethnicity, Institutional Ownership, and Independent Board of Commissioners on Sustainability Reporting with Profitability as a Moderating Variable - Dirvi Surya Abbas; Abduh Hafizh Rabbani; Muhamad Rafli (Universitas Muhammadiyah Palembang, 2025)
This study aims to empirically examine the effects of CEO Ethnic, Institutional Ownership and the Independent Board of Commissioners on Sustainability Reporting with Profitability as a moderating variable. The research population comprises all mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2018- 2022. Using a purposive sampling technique, the study collects 50 samples across those years. Researches obtained second data from financial reports and annual reports published on the official website of the respective company. The study conducts a panel data logistic regression analysis using EViews software. The results reveal that CEO Ethnic, Independent Board of Commissioners do not significantly influence Sustainability Reporting. In contrast, Institutional Ownership has a positive effect. Furthermore, Profitability weakens the influence of CEO Ethnic and the Independent Board of Commissioners on Sustainability Reporting, while strengthening the relationship between Institutional Ownership and Sustainability Reporting.